The chemistries and consequences of DNA and RNA methylation and demethylation - Traube, Franziska R. (RNA Biol, 2017)
Chemical modification of nucleobases plays an important role for the control of gene expression on different levels. That includes the modulation of translation by modified tRNA-bases or silencing and reactivation of genes by methylation and demethylation of cytosine in promoter regions. Especially dynamic methylation of adenine and cytosine is essential for cells to adapt to their environment or for the development of complex organisms from a single cell. Errors in the cytosine methylation pattern are associated with most types of cancer and bacteria use methylated nucleobases to resist antibiotics. This Point of View wants to shed light on the known and potential chemistry of DNA and RNA methylation and demethylation. Understanding the chemistry of these processes on a molecular level is the first step towards a deeper knowledge about their regulation and function and will help us to find ways how nucleobase methylation can be manipulated to treat diseases.